2020
DOI: 10.1111/dmcn.14698
|View full text |Cite
|
Sign up to set email alerts
|

Puberty and menarche in young females with cerebral palsy and intellectual disability: a qualitative study of caregivers’ experiences

Abstract: To explore experiences of parents of young females with cerebral palsy (CP) and intellectual disability at the onset of puberty. METHOD This was a phenomenological qualitative study. We conducted phone interviews of parents of young females with CP and intellectual disability who had been seen in the CP center at a freestanding children's hospital within the prior 2 years. Inclusion criteria were English-speaking parents of young females who had combined diagnoses of CP and intellectual disability. Interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A comparison of demographic and menstruation characteristics of adolescent and adult CP groups is shown in table II. The median age of adolescent CP groups was 16.5 (11)(12)(13)(14)(15)(16)(17)(18) years and adult CP groups were 23.5 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) years. The median age of the adult CP group was higher than the adolescent group (p>0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of demographic and menstruation characteristics of adolescent and adult CP groups is shown in table II. The median age of adolescent CP groups was 16.5 (11)(12)(13)(14)(15)(16)(17)(18) years and adult CP groups were 23.5 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) years. The median age of the adult CP group was higher than the adolescent group (p>0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In a meta-analysis published in 2019, it was reported that there is limited evidence about the menstrual status and hygiene needs of individuals with mental or physical disabilities, and disability rights and sociality can be neglected by ignoring this part of life (17). Studies on menstrual health in the CP population were mostly focused on the thoughts and experiences of caregivers (17)(18)(19)(20). Therefore, studies investigating the menstruation characteristics of women with CP who have good GMFCS-ER levels and can communicate are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, individuals with cerebral palsy can feel that their opinions, perceptions, desires, or rights are neglected (31). An example of topic for which there has been progress but remains much to achieve is reproductive health (32). In many people with cerebral palsy, particularly in children, the right for autonomy is exerted by a third who represents the patients, often the persons who take decisions on their behalf.…”
Section: An Ethical Approachmentioning
confidence: 99%
“…Little is known about the experiences of young females with cerebral palsy and intellectual disability as they transition through puberty because they have largely been excluded from research studies, prompting a team from Boston, US, to examine this topic by interviewing parents of daughters aged 14-24 years. 3 Despite homogeneity in functional ability, there was marked variation in parental perception of the significance of puberty for their daughters. Families often learned about reproductive health from informal social networks.…”
mentioning
confidence: 99%